Diversity and Genetic Association Analysis of Dry Chillies (Capsicum annuum L.) of Northern India for Yield and Biochemical Traits - Verma, Garima; Vikram, Amit; Gupta, Meenu (International Journal of Bio-resource and Stress Management, 2022)
A study was conducted at the Experimental Farm of Department of Vegetable Science, Dr Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan (HP), India during the year 2018 (May–October) to screen twenty-one (21) genotypes of chilli for thirteen characters including yield and total capsaicin content. The evaluation was done in a randomized block design with three replications. Sufficient genetic variability was found for all characters. Correlation analysis revealed a positive significant correlation of fresh ripe yield plant-1 with the number of red fruits plant-1 (0.842*), days to fresh ripe maturity (0.394*), dry yield as percentage of fresh ripe (0.386*), days to 50 % flowering (0.384*), plant height (0.374*) and days to green fruit maturity (0.352*). The number of red fruits plant-1 (0.440*) had a positive significant correlation with total capsaicin content. Path analysis revealed a positive direct effect of number of red fruits plant-1 (0.698) on fresh ripe yield followed by days to green fruit maturity (0.372), number of seeds fruit-1 (0.218), average red fruit weight (0.168), dry yield as percentage of fresh ripe (0.111), plant height (0.111) and red fruit length (0.007) whereas total capsaicin content in dry chilli had the positive direct correlation with days to 50% flowering, days to fresh ripe maturity, number of fruits plant-1 and 1000 seed weight. Finally, it was revealed that the selection of genotypes bearing many small-thick fruits would be the most suitable criterion for selecting a population having high capsaicin content and fruit yield.